Prismatomeris fragrans E.T. Geddes (Rubiaceae) - a new record for the flora of Viet Nam - Bach, Tran The; Quang, Bui Hong; Choudhary, Ritesh Kumar; Hai, Do Van; Diep, Tran Thi Ngoc; Lee, Joongku (Bangladesh Journal of Plant Taxonomy, 2015)
Not available. Bangladesh J. Plant Taxon. 22(2): 147-149, 2015 (December)